Activating the unfolded protein response in osteocytes causes hyperostosis consistent with craniodiaphyseal dysplasia. (29th August 2017) - Chan, Wilson Cheuk Wing; Tsang, Kwok Yeung; Cheng, Yin Wo; Ng, Vivian Chor Wing; Chik, Halina; Tan, Zhi Jia; Boot-Handford, Raymond; Boyde, Alan; Cheung, Kenneth Man Chee; Cheah, Kathryn Song Eng; Chan, Danny
Abstract: Bone remodeling is a balanced process between bone synthesis and degradation, maintaining homeostasis and a constant bone mass in adult life. Imbalance will lead to conditions such as osteoporosis or hyperostosis. Osteoblasts build bone, becoming embedded in bone matrix as mature osteocytes. Osteocytes have a role in sensing and translating mechanical loads into biochemical signals, regulating the differentiation and activity of osteoblasts residing at the bone surface through the secretion of Sclerostin (SOST), an inhibitor of WNT signaling. Excessive mechanical load can lead to activation of cellular stress responses altering cell behavior and differentiation. The unfolded protein response (UPR) is a shared pathway utilized by cells to cope with stress stimuli. We showed that in a transgenic mouse model, activation of the UPR in early differentiating osteocytes delays maturation, maintaining active bone synthesis. In addition, expression of SOST is delayed or suppressed; resulting in active WNT signaling and enhanced periosteal bone formation, and the combined outcome is generalized hyperostosis. A clear relationship between the activation of the unfolded protein response was established and the onset of hyperostosis that can be suppressed with a chemical chaperone, sodium 4-phenobutyrate (4-PBA). As the phenotype is highly consistent with craniodiaphyseal dysplasia (CDD; OMIM 122860), we propose activation of the UPR could be part of the disease mechanism for CDD patients as these patients are heterozygous for SOST mutations that impair protein folding and secretion. Thus, therapeutic agents ameliorating protein folding or the UPR can be considered as a potential therapeutic treatment.